1997
DOI: 10.1183/09031936.97.10122716
|View full text |Cite
|
Sign up to set email alerts
|

The CD4/CD8 ratio in BAL fluid is highly variable in sarcoidosis

Abstract: T Th he e C CD D4 4/ /C CD D8 8 r ra at ti io o iin n B BA AL L f fl lu ui id d i is s h hi ig gh hl ly y v va ar ri ia ab bl le e i in n s sa ar rc co oi id do os si is s S.P. Kantrow*, K.C. Meyer**, P. Kidd*, G. Raghu* The CD4/CD8 ratio in BAL fluid is highly variable in sarcoidosis. S.P. Kantrow, K.C. Meyer, P. Kidd, G. Raghu. ERS Journals Ltd 1997. ABSTRACT: Patients with pulmonary sarcoidosis frequently have increased numbers of lymphocytes and a high ratio of CD4+ to CD8+ T-lymphocytes (CD4/CD8 ratio) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
72
1
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(85 citation statements)
references
References 43 publications
6
72
1
6
Order By: Relevance
“…Since the 1980s, several studies analysing the role of the percentage of BALF lymphocytes and the CD4/CD8 ratio have been performed with diverse results [4][5][6][7]. Since the late 1990s, however, there has been increasing evidence that neutrophilic alveolitis may play an important role in the outcome of sarcoidosis.…”
mentioning
confidence: 99%
“…Since the 1980s, several studies analysing the role of the percentage of BALF lymphocytes and the CD4/CD8 ratio have been performed with diverse results [4][5][6][7]. Since the late 1990s, however, there has been increasing evidence that neutrophilic alveolitis may play an important role in the outcome of sarcoidosis.…”
mentioning
confidence: 99%
“…In addition, it is known that the differentiation of Tcells is closely related to the cytokines (Huang et al, 2014) and many cytokines are secreted by T-cells (Scott, 1993). The CD4+/CD8+ ratio can be used to provide a convenient standard for changes in cellular immune status during disease, nutritional stress, and auto-immune problems (Kantrow et al, 1997). In the present study, the CD4+/CD8+ ratio in the AFB 1 group showed a decreased tendency compared with the control group, but without apparent difference (p> 0.05) (Table 2) in the AFB 1 group during the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Several prospective clinical trials have confirmed the feasibility, safety and efficacy of SBRT, consistently reporting local control rates of 80-95%, comparable to surgical resection [1][2][3], although assessment of response is more complicated than it is following surgery [3]. Radiographic changes following SBRT differ from those following conventional RT, suggesting a unique histological response, and characterisation of these changes is a clinical challenge.…”
Section: To the Editorsmentioning
confidence: 99%
“…Although BAL lymphocytosis is not a universal finding in sarcoidosis [2], the aforementioned studies included only patients with alveolar lymphocytosis. Among our sarcoidosis patients, five (29%) out of 17 patients had a lymphocyte percentage ,10%.…”
Section: To the Editorsmentioning
confidence: 99%
See 1 more Smart Citation